2004
DOI: 10.1080/15227950490923651
|View full text |Cite
|
Sign up to set email alerts
|

Congenitally Corrected Transposition of the Great Arteries With Ebstein Malformation and Hypoplasia of the Aortic Arch in a Fetus

Abstract: u Congenitally corrected transposition of the great arteries is not uncommonly associated with Ebstein' s malformation of its left-sided tricuspid valve. The recognition of this rare association in the fetus is important because its postnatal prognosis is guarded. The present case report illustrates fetal echocardiographic clues to the diagnosis that include mesocardia and apically displaced attachment of the left-sided atrioventricular valve to the ventricular septum at four-chamber view.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…In two there was a congenitally corrected transposition of the great arteries. The association of fetal congenitally corrected transposition of the great arteries and Ebstein's anomaly of the tricuspid valve has previously been reported . In the third fetus we observed a septated cystic hygroma in the nuchal area.…”
Section: Discussionsupporting
confidence: 55%
“…In two there was a congenitally corrected transposition of the great arteries. The association of fetal congenitally corrected transposition of the great arteries and Ebstein's anomaly of the tricuspid valve has previously been reported . In the third fetus we observed a septated cystic hygroma in the nuchal area.…”
Section: Discussionsupporting
confidence: 55%
“…When ccTGA is associated with an Ebstein anomaly, the aorta is often hypoplastic as a consequence of the presence of tricuspid regurgitation (TR) which contributes to a low anterograde flow in the ascending aorta prenatally and thereby to an aortic arch abnormality . A literature review regarding the anatomic characteristics of the right aortic arch reported no association between this anomaly and ccTGA.…”
Section: Discussionmentioning
confidence: 99%
“…In this setting a compromise of anterograde flow from the systemic ventricle to the aorta may result due to an aortic arch obstruction . The combination of ccTGA with Ebstein anomaly and aortic hypoplasia is rare and is correlated with a poor prognosis . We report a unique case of a neonate with a diagnosis of ccTGA, Ebstein anomaly, and hypoplastic right sided arch, and describe its operative management.…”
mentioning
confidence: 99%